Hybridization and genetic introgression patterns between two South American catfish along their sympatric distribution range - do Prado, Fernanda Dotti [UNESP]; Fernandez-Cebriï¿½n, Raquel; Hashimoto, Diogo Teruo [UNESP]; Senhorini, Josï¿½ Augusto; Foresti, Fausto [UNESP]; Martï¿½nez, Paulino; Porto-Foresti, Fï¿½bio [UNESP] (Springer Nature, 2017)
The presence of introgressive hybridization in the wild, especially that resulting from human interference, can have negative impacts on biodiversity. Genetic tools provide essential information for species and hybrid identification, facilitating the conservation of natural resources. Here, we tested a set of markers to precisely elucidate introgressive hybridization between Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum, two South American catfishes. New microsatellites showed high interspecific genetic divergence, and simulated data demonstrated the high power of STRUCTURE and NEWHYBRIDS for hybrid identification and classification, especially when all 11 nuclear markers were used. The investigation of real populations suggested that natural hybridization is rare. Otherwise, different hybridization scenarios were observed in two wild populations: one involving advanced backcrosses and the other involving high admixture. Our data represent the first detailed evaluation of genetic introgression between these species in Parana and Paraguay Basins and suggest that genetic contamination is occurring through F1 hybrids from aquaculture facilities. The results also provide a useful set of markers for monitoring escapees to aid in the conservation of the wild population and sustainable aquaculture. Additionally, species genotypic data are freely available to be used in the future as “parental species reference” in Bayesian methods assignments.
Keywords: Bayesian; Genetic contamination; Microsatellites; Pimelodidae; Pseudoplatystoma